PENGARUH KONSELING KELOMPOK TERHADAP PENURUNAN MASALAH DIRI PRIBADI SISWA SMA NEGERI 6 PADANG - Sefni Rama Putri (Universitas Sultan Ageng Tirtayasa, 2017)
Data obtained from the processing of persond self-description of the problem before the students werw given a group counseling services are in many categorys as many as 1 student, moderate category as many as 11 students, less category as many as 3 students, and few category as many as 1 student. Meanwhile the description of the self problem decrease after given the group counseling services an many categorys as many as 0 student, moderate category as many as 1 student, less category as many as 10 students, and few category as many as 5 students. Based on the calculation result obtained r² values = 0,22 it means there are 22% group counseling services contribute to the decline of students personal problems themselves. Based on the description above there is a significant difference between the decrease of students personal problems themselves before and after the implementation of group conseling services.Keywords: Group counseling, Self problem.